Total Flavonoids of Engelhardia roxburghiana Wall. Leaves Alleviated Foam Cells Formation through AKT/mTOR‐Mediated Autophagy in the Progression of Atherosclerosis. Issue 9 (4th August 2021) - Wei, Jie; Huang, Liangliang; Li, Dongmei; He, Junhui; Li, Yanjing; He, Fei; Fang, Weirong; Wei, Guining
Abstract: Engelhardia roxburghiana Wall. is a traditional Chinese medicine used for treating cardiovascular diseases. Our previous study has implicated potential effects of total flavonoids of Engelhardia roxburghiana Wall. (TFER) against hyperlipidemia. The aim of the study is to uncover the effects and underlying mechanisms of TFER on foam cells formation after atherosclerosis. We used high fat diet (HFD) induced Apoe‐/‐ mice and oxidized density lipoprotein (ox‐LDL) induced THP‐1 cells to mimic process of atherosclerosis in vivo and in vitro, respectively. Lipid accumulation, inflammation response, autophagosomes formation and expressions of autophagy related target genes were assessed. Our present study demonstrated TFER (500 mg/kg) alleviated macrophage infiltration and lipid accumulation in thoracic aortas of HFD‐treated mice. In ox‐LDL‐treated THP‐1 cells, MDC staining and Western blot analysis all indicated that the TFER (200 μg/ml) reduced foam cells formation and IL‐1β releasing, activated autophagy through suppressing AKT/mTOR signaling, significantly regulating expressions of AKT, p‐AKT, mTOR, p‐mTOR, Beclin 1, LC3‐II, p62. It is suggested that TFER alleviated atherosclerosis progression in vivo and in vitro through reducing foam cells formation and inflammatory responses, and the possible mechanism may be due to the activation of macrophage autophagy by inhibiting AKT and mTOR phosphorylation. Abstract :